To eliminate trachoma: Azithromycin mass drug administration coverage and associated factors among adults in Goro district, Southeast Ethiopia. - Tadele Feyisa; Desalegn Bekele; Birhanu Tura; Ahmednur Adem; Fikadu Nugusu (Public Library of Science (PLoS), 2022)
Background Globally, although effective prevention strategies and treatment are available, trachoma remains the major cause of infectious loss of sight. Trachoma is a predominant neglected disease in Ethiopia, and there is a 40.4% prevalence of active trachoma in the Goro district, Southeast Ethiopia. World Health Organization (WHO) recommends azithromycin mass treatment of at least 80% coverage to eliminate trachoma, even though the coverage of azithromycin mass treatment has not been studied yet in depth. Thus, this study aimed to assess the coverage and factors influencing azithromycin mass treatment uptake among adults in Goro district, Southeast Ethiopia. Methods A community-based cross-sectional study was conducted from April 1st to April 30th, 2021 among all adults aged 15 years old and above. The multistage sampling technique was used to select 593 study respondents. A structured interviewer-administered questionnaire was used. Data were entered into Epi-Data version 3.1 and analyzed using SPSS version 23.0 software. Descriptive analysis and binary logistic regression analysis were used to analyze the data. Adjusted odds ratios (AOR) along with a 95% confidence interval (CI) and p-value < 0.05 were used to declare the strength and the significance of association, respectively. Results/principal findings Five hundred and seventy eight study participants with a 97% response rate were included. The proportion of azithromycin mass drug administration coverage was found to be 75.80%; 95% CI: (72%-79%) in this study. Having better knowledge about trachoma (AOR = 2.36; 95% CI: 1.19-4.70), having better knowledge about azithromycin mass treatment (AOR = 4.19; 95% CI: 2.19-7.98), being educated (AOR = 7.20; 95% CI: 1.02-51.09), a campaign conducted at the quiet time (off-harvesting/planting season) (AOR = 6.23; 95% CI: 3.23-11.98), heard about the serious adverse effect from others (AOR = 0.25; 95% CI: 0.10-0.59) and being a volunteer to take azithromycin in the next campaign (AOR = 5.46; 95% CI: 2.76-10.79) were significantly associated with azithromycin mass drug administration coverage. Conclusions/significance The proportion of azithromycin mass treatment coverage of this study was lower than the WHO minimum target coverage. Thus, strengthening awareness, enhancing azithromycin mass trachoma treatment messages, and conducting campaigns off-season outside of harvesting and planting time should be prioritized in the future to meet the 2030 Sustainable Development Goal (SDG) target.